ENHANCING DIGITAL LITERACY SKILLS THROUGH GAMIFICATION ACTIVITIES OF INTERMEDIATE LEVEL STUDENTS - Vakhobova Zokhidakhan Abdumajit qizi; Scientific Advisor: Moydinova Elmira Kamariddinovna (Bright Mind Publishing, 2025)
This article explores how gamification can be effectively used to enhance digital literacy skills among intermediate-level students. It discusses the concept of gamification, its theoretical foundations, and how it can be integrated into educational settings to make digital literacy instruction more engaging and effective. Through an analysis of gamified platforms, teaching strategies, and real-world classroom examples, the article highlights how game elements such as points, challenges, and leaderboards can boost motivation, participation, and skill development. The article also addresses potential challenges and offers practical recommendations for educators. The study concludes that gamification, when thoughtfully applied, can significantly improve students’ digital competencies and overall learning experience.
Keywords: Gamification, digital literacy, intermediate-level students, educational technology, learner engagement, game-based learning, digital skills, motivation, EFL learners, classroom innovation.